Coevolution: plant-microorganism. - Thrall, P.; Watkin, Elizabeth; Burdon, J. (Nature Publishing Group, 2001)
Plant-microorganism coevolutionary interactions cover a very wide arena involving the interactions between plants and many bacteria, fungi, viruses and nematodes.